Changing patterns in place of cancer death in England: a population-based study. - Wei Gao; Yuen K Ho; Julia Verne; Myer Glickman; Irene J Higginson; GUIDE_Care project (PLoS Medicine, 2013)
Background Most patients with cancer prefer to die at home or in a hospice, but hospitals remain the most common place of death (PoD).This study aims to explore the changing time trends of PoD and the associated factors, which are essential for end-of-life care improvement. Methods and findings The study analysed all cancer deaths in England collected by the Office for National Statistics during 1993-2010 (n = 2,281,223). Time trends of age- and gender-standardised proportion of deaths in individual PoDs were evaluated using weighted piecewise linear regression. Variables associated with PoD (home or hospice versus hospital) were determined using proportion ratio (PR) derived from the log-binomial regression, adjusting for clustering effects. Hospital remained the most common PoD throughout the study period (48.0%; 95% CI 47.9%-48.0%), followed by home (24.5%; 95% CI 24.4%-24.5%), and hospice (16.4%; 95% CI 16.3%-16.4%). Home and hospice deaths increased since 2005 (0.87%; 95% CI 0.74%-0.99%/year, 0.24%; 95% CI 0.17%-0.32%/year, respectively, p<0.001), while hospital deaths declined (-1.20%; 95% CI -1.41 to -0.99/year, p<0.001). Patients who died from haematological cancer (PRs 0.46-0.52), who were single, widowed, or divorced (PRs 0.75-0.88), and aged over 75 (PRs 0.81-0.84 for 75-84; 0.66-0.72 for 85+) were less likely to die in home or hospice (p<0.001; reference groups: colorectal cancer, married, age 25-54). There was little improvement in patients with lung cancer of dying in home or hospice (PRs 0.87-0.88). Marital status became the second most important factor associated with PoD, after cancer type. Patients from less deprived areas (higher quintile of the deprivation index) were more likely to die at home or in a hospice than those from more deprived areas (lower quintile of the deprivation index; PRs 1.02-1.12). The analysis is limited by a lack of data on individual patients' preferences for PoD or a clinical indication of the most appropriate PoD. Conclusions More efforts are needed to reduce hospital deaths. Health care facilities should be improved and enhanced to support the increased home and hospice deaths. People who are single, widowed, or divorced should be a focus for end-of-life care improvement, along with known at risk groups such as haematological cancer, lung cancer, older age, and deprivation. Please see later in the article for the Editors' Summary.